Bild-Raum-Handlung. Perspektiven der Archäologie - Dally, Ortwin (Topoi, 2012)
Images are more than just objects to be observed. In all periods they have had a direct influence on the way we perceive things and act, in particular in the course of ceremonies. In this volume, various archaeological disciplines consider a number of case studies of the relationships between works of art, spaces and actions in past cultures? including the Nasca-Palpa glyphs in South America, the Stone Age site of G